Analysis of Global Stability of Endemic Equilibrium of HIV/AIDS with Drug-resistant Compartment Using Lasalle’s Invariant Principle - Ale, S. (Asian Journal of Mathematical Sciences(AJMS), 2023)
All over the world, human immunodeficiency virus (HIV)/AIDS has continued to be a major threat to humanity resulting in death of millions annually across the globe despite countless research works and readiness of anti-retroviral drugs as means of combating the menace. This research formulated a mathematical model to study the spread dynamics of HIV/AIDS in the presence of highly effective antiretroviral treatment (HART) incorporating HART resistance compartment. The basic reproduction number was obtained using the next generation matrix method. The endemic equilibrium of the model was analyzed using the Lasalle’s invariant principle and it was found to be globally asymptotically stable.